Characterization and crystallization of proton-dependent oligopeptide transporters - Svenja Hornung (2015)
POTs (proton-dependent oligopeptide transporters) are integral membrane proteins and essential for maintaining homeostasis in cells by switching between two major conformations during the transport cycle. Di- and tripeptides as well as some small peptide like compounds are recognized and transported across the membrane. This fact leads to the pharmacological interest in these transporters for drug delivery. In humans two transporters, PepT1 and PepT2, occur. So far only structures of five bacterial homologues are available. Eukaryotic POTs exist of 12 transmembrane helices whereas prokaryotic POTs have two additional transmembrane helices. It was possible to clone different prokaryotic transporter constructs into pET expression vectors as well as the PepT-like transporter (CtPOT) of Chaetomium thermophilum, a thermophilic eukaryote, and the human PepT2. Two transporters of Shewanella oneidensis (PepTSo2) modified with the thermostabilized apocytochrome b562RIL as well as the CtPOT and PepT2 were expressed in Escherichia coli cells. These transporters except PepT2 were solubilized and purified. Crystals were obtained of all proteins but it was not possible to solve any structure so far due to limited crystal diffraction.
Keywords: POT; POT; membrane proteins